2022
DOI: 10.3389/fchem.2022.1036683
|View full text |Cite
|
Sign up to set email alerts
|

An “on-off-on” fluorescence probe for glyphosate detection based on Cu2+ modulated g-C3N4 nanosheets

Abstract: The analysis of glyphosate is essential to agricultural production, environment protection and public health. Herein, we proposed a fast and convenient “on-off-on” fluorescence platform for sensitive detection of glyphosate via Cu2+ modulated g-C3N4 nanosheets. The fluorescence of the system was quenched by Cu2+. With the presence of glyphosate, the fluorescence could be restored due to the formation of Cu2+- glyphosate complex. The proposed method was cost-effective with label-free and enzyme-free. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…There are many sensors that have been reported for GLY detection. For example, Hong et al , 15 Qin et al 23 and Kimani et al 24 reported nano-sensors; their detection limit can reach 0.035–10 ng mL −1 . Wang et al 16 reported a method with carbon dots as fluorescent sensor, whose detection limit can reach 16 ng mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…There are many sensors that have been reported for GLY detection. For example, Hong et al , 15 Qin et al 23 and Kimani et al 24 reported nano-sensors; their detection limit can reach 0.035–10 ng mL −1 . Wang et al 16 reported a method with carbon dots as fluorescent sensor, whose detection limit can reach 16 ng mL −1 .…”
Section: Resultsmentioning
confidence: 99%